Development and application of in vitro approaches to assess the interactions of aerosolised drugs with pulmonary mucus - Alqahtani, Safar (2019)
Studies centered on pulmonary drug delivery have primarily focused on new device technologies to improve the generation of aerosols and their deposition in the respiratory system. Although considerable progress has been made in this field, no significant superior treatment of respiratory diseases has been achieved in recent times. One of the principal reasons is a scarcity in knowledge concerning inhaled/aerosol drug fate post-deposition in the lungs. The first barrier encountered by inhaled drugs in the pulmonary system is the mucus layer. This plays a protective role that is believed to be largely achieved by its ability to act as a physical barrier but also hinders molecular diffusion. The impeding nature of the mucus on aerosolised drug permeation is poorly understood. Indeed, the effects of direct interactions between mucus and inhaled drugs have been largely overlooked and most of the available evidence on mucus-drug interactions are related to the gastrointestinal tract. In this doctoral thesis, the main aim was to gain a better understanding of the relationship between the physicochemical properties of aerosolised pulmonary agents and their diffusion across the pulmonary mucus layer. This knowledge would provide valuable information for the development of more effective pulmonary agents. The first objective was to develop and characterise an in vitro mucus model suitable for drug permeation studies. That was comprised of a thin mucus layer derived from pig trachea covering the semi-permeable membrane of Transwell® inserts. Rheometric measurements on pig tracheal mucus secretions after a cleaning procedure to remove blood contaminants demonstrated that the obtained mucus was non-Newtonian. Furthermore, cryogenic-scanning electron microscopy (cryo-SEM) revealed pore sizes with diameters of ∼400 ± 200 nm. The barrier properties of the mucus model were verified by measuring the diffusion of various fluorescent dyes across mucus layers coating the Transwell® inserts. This revealed that the physicochemical properties of the compounds influenced their permeation rate with lipophilic dyes preferentially binding to the mucus layer. A global metabolic profiling approach was applied to characterise the low molecular weight compounds present in pig tracheal mucus before and after the cleaning procedure. A total of 816 metabolites were common to both sets of raw and cleaned mucus samples. Approximately 50% of those were lipids, products of amino acid metabolism and carbohydrate metabolism, which was in line with the previously reported composition of human bronchial mucus. A deposition system consisting of a Penn-Century MicroSprayer® mounted into a holder glass desiccator was successfully assembled to allow aerosolisation of test molecules at the surface of the mucus layers. After optimisation of the distance between the MicroSprayer® and the Transwell® inserts, the volume of the spray and the geometrical arrangement of the Transwell® inserts underneath the spray, a reproducible dose could be delivered onto four Transwell® inserts. Ipratropium bromide, glycopyrronium bromide, salbutamol sulphate, formoterol and indacaterol maleate were chosen as model pulmonary agents to investigate the effect of drug physicochemical properties on their interactions with airway mucus using the in-vitro mucus model and aerosoliser system previously developed. The extent of drug retention within the mucus layer varied between the compounds tested. Although no significant correlation could be established due to the low number of drugs studied, logP appeared the most important physico-chemical parameter driving drug affinity for pulmonary mucus. This PhD thesis has led to the development of simple in vitro systems to investigate the effect of the mucus layer on drug fate in the lungs and has identified mucus as a possible barrier to drug diffusion, in particular, for lipophilic compounds.